2007
DOI: 10.1093/llc/fqm042
|View full text |Cite
|
Sign up to set email alerts
|

Killer Applications in Digital Humanities

Abstract: The emerging discipline of "digital humanities" has been plagued by a perceived neglect on the part of the broader humanities community. The community as a whole tends not to be aware of the tools developed by DH practitioners (as documented by the recent surveys by Siemens et al.), and tends not to take seriously many of the results of scholarship obtained by DH methods and tools. This paper argues for a focus on deliverable results in the form of useful solutions to common problems that humanities scholars s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 3 publications
0
14
0
1
Order By: Relevance
“…In the humanities, “a straw poll showed that half of [the discussants at the Institute for Advanced Technologies in the Humanities Summit 2006] wanted to build this kind of tool, and all wanted to use it” (Juola, , p. 80). Despite this expressed desire to have annotation capabilities, most scholars do not use digital annotation systems currently (Juola, ). Humanities sites, such as the Online Chopin Variorum Edition, have not had success in attracting end users to participate and contribute annotations (Bradley & Vetch, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the humanities, “a straw poll showed that half of [the discussants at the Institute for Advanced Technologies in the Humanities Summit 2006] wanted to build this kind of tool, and all wanted to use it” (Juola, , p. 80). Despite this expressed desire to have annotation capabilities, most scholars do not use digital annotation systems currently (Juola, ). Humanities sites, such as the Online Chopin Variorum Edition, have not had success in attracting end users to participate and contribute annotations (Bradley & Vetch, ).…”
Section: Discussionmentioning
confidence: 99%
“…meeting in 2005. Juola (2006) also decried this lack of user studies, identifying a "mismatch of expectations between the expected needs of audience (market) for the tools and the community's actual needs" as a likely source of much unrealized potential with digital texts (p. 5). NINCH similarly found that digital texts are often erroneously designed around assumptions about user's needs based on "existing usage of analog resources" (2003).…”
Section: The Lack Of Digital Humanities User Studiesmentioning
confidence: 99%
“…They do remain approaches that appear to have had limited impact thus far, however, and there is no evidence of a change in the way in which most individuals deal with the actual text itself. 27 Some of these themes of digital humanities are developed in Juoal 2008 . The question of how the Muslim world makes use of the information and communication technologies to religious ends, and what impact that has on Muslim modes of religious practice through these processes of production and consumption is well illustrated by the Qur'ān on the Internet. As may be seen in so many other sites that allow access to the Qur'ān, in many cases nothing has changed in terms of the approach to textual study and analysis from when texts were available solely as printed books or manuscripts.…”
Section: Directions For the Future?mentioning
confidence: 99%